2006
DOI: 10.1124/jpet.105.097469
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolism of (Nitrooxy)butyl Ester Nitric Oxide-Releasing Compounds: Comparison with Glyceryl Trinitrate

Abstract: We investigated the in vitro metabolism of two (nitrooxy)butyl ester nitric oxide (NO) donor derivatives of flurbiprofen and ferulic acid, [1,1Ј-biphenyl]-4-acetic acid-2-fluoro-␣-methyl-4-(nitrooxy)butyl ester (HCT 1026) and 3-(4-hydroxy-3-methoxyphenyl)-2-propenoic acid 4-(nitrooxy)butyl ester (NCX 2057), respectively, in rat blood plasma and liver subcellular fractions compared with (nitrooxy)butyl alcohol (NOBA) and glyceryl trinitrate (GTN). HCT 1026 and NCX 2057 undergo rapid ubiquitous carboxyl ester hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Third, S-nitrosylation, an unambiguous marker of NO action, following exposure to NO-NSAIDs has been repeatedly identified [43]. Finally, Govoni et al using electron paramagnetic resonance demonstrated that NOflurbiprofen generated NO in erythrocytes, with hemoglobin mediating this biotransformation [44]. Their work and that of others suggests that the NO-releasing moiety (−ONO 2 ) undergoes 1 e − reduction to NO 2 − , which is then either converted to NO or oxidized to NO 3 − .…”
Section: No As the Mediator Of The Action Of No-nsaidsmentioning
confidence: 99%
“…Third, S-nitrosylation, an unambiguous marker of NO action, following exposure to NO-NSAIDs has been repeatedly identified [43]. Finally, Govoni et al using electron paramagnetic resonance demonstrated that NOflurbiprofen generated NO in erythrocytes, with hemoglobin mediating this biotransformation [44]. Their work and that of others suggests that the NO-releasing moiety (−ONO 2 ) undergoes 1 e − reduction to NO 2 − , which is then either converted to NO or oxidized to NO 3 − .…”
Section: No As the Mediator Of The Action Of No-nsaidsmentioning
confidence: 99%
“…Although much of nitroglycerin's pharmacology is known, the mechanisms through which nitroglycerin acts on the endothelium and the heart as well as the enzymatic pathways leading to its bioactivation are still controversial and under intense investigation. A number of hypotheses for nitroglycerin bioconversion in vivo have been formulated, implicating a multitude of enzymes such as GST (6,7), oxidoreductases (8), and mitochondrial aldehyde dehydrogenase (9,10) in the bioconversion of nitroglycerin to NO and/or other vasoactive compounds. For example, GST has been shown to catalyze the transnitration of lower thiols in the presence of nitroglycerin (6,7).…”
mentioning
confidence: 99%
“…A number of hypotheses for nitroglycerin bioconversion in vivo have been formulated, implicating a multitude of enzymes such as GST (6,7), oxidoreductases (8), and mitochondrial aldehyde dehydrogenase (9,10) in the bioconversion of nitroglycerin to NO and/or other vasoactive compounds. For example, GST has been shown to catalyze the transnitration of lower thiols in the presence of nitroglycerin (6,7). Xanthine oxidase and mitochondrial aldehyde dehydrogenase (which are closely related oxidoreductases) have been found to mediate nitroglycerin reduction to nitrite (11) and NO itself (8,10).…”
mentioning
confidence: 99%
“…This mechanism, along with soluble guanylyl cyclase desensitization and activation of oxidative stress, has been described as mediating ISMN-induced tolerance (Minamiyama et al, 2004;Daiber and Munzel, 2015). However, this mechanism may not be as important for NCX1404 because similar NO-donating compounds were reported to rely on different bioactivation pathways compared with ISMN (Govoni et al, 2006).…”
Section: Discussionmentioning
confidence: 99%